2021
DOI: 10.3390/ijms22126284
|View full text |Cite
|
Sign up to set email alerts
|

SRPassing Co-translational Targeting: The Role of the Signal Recognition Particle in Protein Targeting and mRNA Protection

Abstract: Signal recognition particle (SRP) is an RNA and protein complex that exists in all domains of life. It consists of one protein and one noncoding RNA in some bacteria. It is more complex in eukaryotes and consists of six proteins and one noncoding RNA in mammals. In the eukaryotic cytoplasm, SRP co-translationally targets proteins to the endoplasmic reticulum and prevents misfolding and aggregation of the secretory proteins in the cytoplasm. It was demonstrated recently that SRP also possesses an earlier unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 169 publications
0
23
0
Order By: Relevance
“…When a secretory or integral membrane protein is translated in the cytosol and the targeting signal (i.e., SP or TMD) emerges from the ribosomal exit tunnel, it is recognized and bound to by SRP [ 46 , 47 , 64 , 65 , 66 , 67 , 68 ] (see Figure 2 ). SRP is a ribonucleoprotein complex consisting of six subunits (SRP9, 14, 19, 54, 68 and 72 m) and a 7S RNA molecule, which assemble into two SRP domains [ 22 , 46 , 48 ].…”
Section: The Sec61 Dependent Pathway For Co- and Post-translational Protein Translocationmentioning
confidence: 99%
See 2 more Smart Citations
“…When a secretory or integral membrane protein is translated in the cytosol and the targeting signal (i.e., SP or TMD) emerges from the ribosomal exit tunnel, it is recognized and bound to by SRP [ 46 , 47 , 64 , 65 , 66 , 67 , 68 ] (see Figure 2 ). SRP is a ribonucleoprotein complex consisting of six subunits (SRP9, 14, 19, 54, 68 and 72 m) and a 7S RNA molecule, which assemble into two SRP domains [ 22 , 46 , 48 ].…”
Section: The Sec61 Dependent Pathway For Co- and Post-translational Protein Translocationmentioning
confidence: 99%
“…Next, the RNC complex is targeted toward the ER membrane. Here, SRP interacts with the SRP receptor (SR) [ 46 , 47 , 64 , 65 , 66 , 67 , 68 ]. The SR then mediates the transfer of the RNC complex to the Sec61 translocon, the central component, and protein-conducting channel of the Sec61 dependent pathway for protein translocation [ 22 , 46 , 47 , 48 ].…”
Section: The Sec61 Dependent Pathway For Co- and Post-translational Protein Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…During protein synthesis, the nascent chain that emerges from the ribosomal tunnel interacts with a number of proteins involved in the correct folding, translocation, and modification of the synthesizing protein. In eukaryotes, secretory proteins are targeted to the ER by the Signal Recognition Particle (SRP) [16,17]. SRP recognizes the signal sequences, additional regions on the N-termini of the emerging secretory protein polypeptide nascent chains, during translation.…”
Section: Depletion Of Srp54 Affects αSyn Expressionmentioning
confidence: 99%
“…SRP conducts mRNA protective function during RAPP in addition to its earlier well-established role as a major protein targeting factor in the cell. SRP, as a targeting factor, is responsible for the first steps in protein transport and correct localization to the ER, plasma membrane, or outside of the cell [16,17]. Previously, we have shown that depletion of the SRP54 subunit of SRP results in a loss of its mRNA protective function, activates the RAPP pathway, and leads to a reduction in the expression of secretory proteins and their mRNAs.…”
Section: Introductionmentioning
confidence: 99%